Clinical profile and outcomes of patients receiving acute renal replacement therapy in the cardiac intensive care unit at a South African referral centre - Mbanga, L.C.; Lunga, N.P.; Musoke, F.; Mfeketho, O.; Badri, M.; Ntsekhe, M.; Mkoko, P. (SA Heart Journal, 2025)
Background: At least a quarter of patients admitted to the cardiac intensive care unit (CICU) will develop acute kidney injury (AKI), and some of these patients receive renal replacement therapy (RRT). The clinical profiles and outcomes of CICU patients receiving RRT in resource constraint settings like South Africa are unknown. Objectives: The objectives of this study were to determine the clinical profiles and outcomes of patients receiving RRT in the CICU in a South African tertiary centre. Methods: In this retrospective study, we included consecutive patients admitted and receiving RRT at the Groote Schuur Hospital CICU from 1 January 2012 - 31 December 2016. Results: During the study period, 3 247 patients were admitted to the CICU, and 46 (1.4%) received RRT. The RRT patients had a mean (SD) age of 52 (17) years, 56% were males, and 65% had a background history of systemic hypertension. Heart failure syndromes accounted for 60.9% of CICU admission in the RRT patient group, followed by acute coronary syndromes and arrhythmias, which accounted for 26.1% and 13.0%, respectively. The RRT patient population had in-hospital and 30-day mortality rates of 58.7% and 60.9%, respectively. Baseline use of angiotensin converting enzyme (ACE) inhibitor or angiotensin receptor blocker (ARB) was associated with a reduced 30-day mortality rate, hazards ratio (HR) 0.43; 95% confidence interval (95% CI) 0.20 - 0.93; p=0.031. In addition, heart failure was associated with an increased 30-day mortality rate, HR 2.52; 95% CI 1.10 - 5.78; p=0.029. Conclusion: In this single-centre study from an upper middle-income country, a small proportion of CICU patients receive RRT. Heart failure syndrome is associated with most RRT patients admitted to the CICU. Patients receiving RRT in CICU have a high inhospital and 30-day mortality.